Emergence of NDM-5-Producing Escherichia coli in a Teaching Hospital in Chongqing, China: IncF-Type Plasmids May Contribute to the Prevalence of blaNDM–5 - Zou, Hua; Jia, Xiaojiong; Liu, Hang; Li, Shuang; Wu, Xianan; Huang, Shifeng (Frontiers in Microbiology, 2020)
The newly emerging NDM-5 confers increased antibiotic resistance and attracts extensive global attention, but the prevalence, dissemination mechanism, and clinical significance of NDM-5 among clinical Escherichia coli (E. coli) infections have not been thoroughly characterized to date. In the present study, 109 unique carbapenem-resistant E. coli (CR-EC) isolates were collected in Southwest China, from 2013 to 2017, among which 41 (37.61%) CR-EC isolates were identified as NDM-5-producers, with most isolates carrying the IncF-type plasmids. Molecular epidemiological studies revealed ST167 being the most common sequence type (ST). Moreover, we described the first report of a clinical CR-EC isolate co-harboring blaKPC–2 and blaNDM–5, which showed a higher level of resistance to carbapenems. In addition, blaNDM–5 plasmid transformation and conjugation indicated that blaNDM–5 itself did confer resistance to carbapenems. Complete sequencing of the blaNDM–5-harboring IncF plasmid revealed highly conserved regions (bleMBL-trpF-tat) and some transposons around blaNDM–5. Our findings revealed a new potential threat of NDM-5-postive CR-EC in mainland China and emphasized an urgent need to control their further spread.